MANAJEMEN NILAI HUBUNGAN MANUSIA DENGAN MANUSIA LAIN DALAM SEGATA “PENAYUHAN” KARYA SUSI RATUBELIA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA LAMPUNG DI SMP - Febri Pirman Prahmudana; Laskar Gema Lambar; Rasyid Rayhan Alfajrie (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study discusses the values of human relationships contained in Segata Penayuhan by Susi Ratubelia and its implications for Lampung language learning in junior high schools. Segata, as one of the forms of Lampung oral literature, not only functions as a medium of entertainment and cultural expression but also conveys meaningful moral messages. This research employs a descriptive qualitative method with stages including data collection, analysis, and presentation of results. The object of study focuses on Segata Penayuhan, emphasizing moral values, particularly human relationships that encompass mutual respect, solidarity, empathy, and ethics in social life. The results of the study show that Segata Penayuhan contains humanistic values relevant to everyday life, such as the importance of maintaining good relationships with others, avoiding prejudice, and fostering togetherness within the community. These values have significant implications for Lampung language learning in junior high schools, as they can serve as teaching materials that introduce students to local cultural heritage while instilling positive character traits. Thus, Lampung language learning based on segata not only enhances students’ understanding of regional literary works but also strengthens cultural identity and nurtures morally upright individuals.